2008
DOI: 10.1350/ijps.2008.10.3.83
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Silence: The Traumatic Circle of Policing

Abstract: Operational police officers often work in traumatic situations. Whilst training and support is provided to officers in these areas in the UK, and some debriefing and counselling is provided, this is not fully effective in addressing the so-called 'attitudinal' problem of the police. We believe that one of the reasons for this is that police training does not adequately address the effects of working in traumatic conditions, and certainly does not take into account new work in the area of post-traumatic stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 5 publications
0
24
0
2
Order By: Relevance
“…While STS is most often associated with treatment providers, recent work has emphasized the importance of STS among other populations, including law enforcement personnel and their family members. Rees and Smith (2008) noted the impact of trauma faced by officers and found that the subsequent coping mechanisms This article not subject to US copyright law.…”
Section: A Longitudinal Examination Of Secondary Traumatic Stress Amomentioning
confidence: 99%
“…While STS is most often associated with treatment providers, recent work has emphasized the importance of STS among other populations, including law enforcement personnel and their family members. Rees and Smith (2008) noted the impact of trauma faced by officers and found that the subsequent coping mechanisms This article not subject to US copyright law.…”
Section: A Longitudinal Examination Of Secondary Traumatic Stress Amomentioning
confidence: 99%
“…Law enforcement officers are one group often reported to experience significantly higher levels of distress compared to the general population due to occupational stressors. As a result, alcohol abuse such as binge drinking (defined as consuming five or more drinks per drinking occasion) among police officers is commonly thought to be at a substantially elevated rate compared to the general public (Naimi et al, 2003;Obst, Davey, & Sheehan, 2001;Rees & Smith, 2008;Swatt, Gibson, & Piquero, 2007). However, some researchers report different findings.…”
mentioning
confidence: 99%
“…While scholarship on trauma and vulnerability of military veterans is now well established (Paulson and Krippner 2007, Tick 2012, Gossman 2015, it is still seen as largely taboo to discuss vulnerability and trauma in relation to policing (Rees andSmith 2008, Rufo 2016), particularly for young white men who see sharing their feelings as ego-threatening (Paskiac and Kelley 2013).…”
Section: Resultsmentioning
confidence: 99%